Co nového přináší nová ekonomika - Volejníková Jolana (Univerzita Pardubice, 2001)
The New Economy - information technologies have colossal importance for progress of economy and economic growth. This article is trying to describe clearly many opportunites for economic development, brought by progress of information technologies. Important changes in effectiveness and productivity of companies, public administration and also employes. The result of these change is increasing ability to compete of whole national economy.
Keywords: nová ekonomika; nové směry; dynamické procesy; nové technologie; hospodářský růst